Anthropometric Characteristics of Young Bocce Athletes in the Raffa Specialty: An Analysis of Physical Parameters in Junior Players of National Level - Fabio Scamardella; Francesca Latino; Maria Giovanna Tafuri (Physical Education Theory and Methodology)
Background. The sport of bocce, and in particular the specialty of Raffa, has seen significant competitive development in recent decades, but the scientific literature on the anthropometric characteristics of athletes, especially among young people, is still limited.